Effect of biochar aging on surface characteristics and adsorption behavior of dialkyl phthalates. (November 2015) - Ghaffar, Abdul; Ghosh, Saikat; Li, Fangfang; Dong, Xudong; Zhang, Di; Wu, Min; Li, Hao; Pan, Bo
Abstract: The implications of biochar aging regarding their material properties as well as their interactions with other contaminants are not vivid. We report the role of biochar aging on sorption behavior of di-alkyl phthalates (PAEs). Biochars used in this study were produced from peanut-shell and their aging was simulated by chemical oxidation. The structural composition and morphology of the obtained biochars, before and after oxidation with HNO3 /H2 SO4, were analyzed by element composition, XPS, DRIFT, and SEM/EDX. Several experimental results unequivocally showed oxygen enrichment in the mixed acid treated samples compared to their precursors. Despite surface area reduction and pore destruction, increased PAEs sorption on oxidized biochar surfaces portrayed existence of strong PAEs binding sites. The adsorption of PAEs on oxidized biochar surface is a cumulative influence of hydrophobic interactions and pi–pi electron donor–acceptor interactions. Our results suggest that imminent aging of biochar upon environmental exposure may change their sorbent properties. Highlights: Oxidized biochars showed increased oxygen content and decreased surface area. SEM/EDX images indicated oxygen enrichment on biochar after oxidation. Di-alkyl phthalates sorption increased after biochar oxidation. Hydrophobic and pi–pi electron donor–acceptor interactions are important. Abstract : Oxidation decreased biochar surface area, but increased their oxygen-containing functional groups and their sorption to di-alkyl phthalates.